CAV1 inhibits metastatic potential in melanomas through suppression of the integrin/Src/FAK signaling pathway - Trimmer, Casey; Whitaker-Menezes, Diana; Bonuccelli, Gloria; Milliman, Janet N; Daumer, Kristin M; Aplin, Andrew E; Pestell, Richard G; Sotgia, Federica; Lisanti, Michael P; Capozza, Franco (Cancer research (Chicago, Ill.), 2010)
Caveolin-1 (CAV1) is the main structural component of caveolae, which are plasma membrane invaginations that participate in vesicular trafficking and signal transduction events. Although evidence describing the function of CAV1 in several cancer types has recently accumulated, its role in melanoma tumor formation and progression remains poorly explored. Here, by using B16F10 melanoma cells as an experimental system, we directly explore the function of CAV1 in melanoma tumor growth and metastasis. We first show that CAV1 expression promotes proliferation, whereas it suppresses migration and invasion of B16F10 cells in vitro. When orthotopically implanted in the skin of mice, B16F10 cells expressing CAV1 form tumors that are similar in size to their control counterparts. An experimental metastasis assay shows that CAV1 expression suppresses the ability of B16F10 cells to form lung metastases in C57Bl/6 syngeneic mice. Additionally, CAV1 protein and mRNA levels are found to be significantly reduced in human metastatic melanoma cell lines and human tissue from metastatic lesions. Finally, we show that following integrin activation, B16F10 cells expressing CAV1 display reduced expression levels and activity of FAK and Src proteins. Furthermore, CAV1 expression markedly reduces the expression of integrin β(3) in B16F10 melanoma cells. In summary, our findings provide experimental evidence that CAV1 may function as an antimetastatic gene in malignant melanoma.